QCr0.8 Cu alloy /S06 stainless steel bimetal structure via In718 multi-interlayer fabricated by laser powder hybrid additive manufacturing - Baopeng Zhang; Wenqi Zhang; Haifeng Xiao; Haihong Zhu; Huanqing Yang; Yun Wang; Baijin Chen (Journal of Materials Research and Technology, 2023)
Fabricating high strength high conductivity (HSHC) Cu alloy inner parts by laser powder bed fusion (LPBF) and high-strength steel out layers on Cu alloy surfaces by laser-direct energy deposition (LDED), e.g., laser powder hybrid additive manufacturing (LPH-AM), has shown promise in the development of rocket engine thrust chambers with large thrust forces. In this study, we successfully fabricated a QCr0.8 HSHC Cu alloy/S06 stainless steel bimetal structure via In718 multi-interlayer using LPH-AM. We investigated the relative density, defects, microstructure, and interfacial characteristics of the bimetal structure in detail. The results indicate that the sample achieved up to 99.9% relative density with no naked defects and good metallurgical bonding at the QCr0.8/In718 and In718/S06 interfaces. The LPH-AM-ed QCr0.8/In718 interface exhibited a combination of columnar and equiaxed dendrites. The vertically combined sample exhibited an average ultimate tensile strength (UTS) and break elongation (EL) of 300.3 ± 10.6 MPa and 15.0 ± 1.4%, respectively, with fracture occurring at the QCr0.8 side. This study provides a new method for fabricating complex-shaped Cu/steel bimetal components, such as rocket engine thrust chambers.